Cardiac Implantable Electronic Devices in Ebstein Anomaly: Management and Outcomes. (28th June 2022) - Tan, Nicholas Y.; Amin, Mustapha; Dearani, Joseph A.; McLeod, Christopher J.; Stephens, Elizabeth H.; Cannon, Bryan C.; Miranda, William R.; Connolly, Heidi M.; Egbe, Alexander; Asirvatham, Samuel J.; Madhavan, Malini
Abstract : Background: Optimal management of cardiac implantable electronic devices (CIEDs) in patients with Ebstein anomaly during tricuspid valve (TV) surgery is unknown. Thus, we aimed to characterize CIED management/outcomes in patients with Ebstein anomaly undergoing TV surgery. Methods: Patients at the Mayo Clinic from 1987 to 2020 with Ebstein anomaly and CIED procedure were reviewed for procedural details, complications, echocardiogram, and lead parameters. Five-year cumulative incidence of CIED complications were estimated using the Kaplan-Meier method. Results: Ninety-three patients were included; 51 were female, and mean age was 40.7±17.5 years. A new CIED was implanted in 45 patients at the time of TV surgery with the majority receiving an epicardial (n=37) CIED. Among 34 patients who had preexisting CIED (11 epicardial, 23 transvenous) at time of TV surgery, 20 had a transvenous right ventricular lead managed by externalizing the lead to the TV (n=15) or extracting the transvenous lead with epicardial lead implantation (n=5). Fourteen patients underwent CIED implantation (4 epicardial, 10 transvenous) without concurrent surgery. Placement of lead across the TV was avoided in 85% of patients. The 5-year cumulative incidence of CIED complications was 24% with no significant difference between epicardial and transvenous CIEDs (26% versus 23%, P =0.96). Performance of lead parameters was similar in epicardial and transvenous leads during median (interquartile range) follow-up of 44.5 (61.1) months. Conclusions: In patients with Ebstein anomaly undergoing TV surgery, the use of epicardial leads and externalization of transvenous leads to the TV can avoid lead placement across the valve leaflets. Lead performance and CIED complications was similar between epicardial and transvenous CIEDs.